Electricity and Lighting Audits at The Bono Pekanbaru Hotel - Ramadhan, Muhammad Fiqri; Aini, Zulfatri (Jurnal Edukasi Elektro, 2023)
Electrical energy is one of the primary sources of energy support in our lives, which is very important in the operation of the hospitality industry, especially in using electronic equipment and air conditioning lighting. Many devices that require electrical energy to operate make energy consumption increase. Therefore, efforts to prevent waste of electricity use need to be made through energy audits as well as energy savings opportunities by performing calculations of Energy Consumption Intensity (ECI) values based on historical data of electrical consumption and performing measurements of light intensity on the lighting system available at The Bono Pekanbaru Hotel. Some rooms still exceed the set ECI value, which can be categorized as wasteful energy. It is necessary to do so energy-saving opportunities while on the lighting system based on the measurement of the light intensity carried out in each room, many rooms that do not meet the lighting standards and the basis of the visual still experience evaporation. This requires an energy audit and a lighting audit. On the important lighting system made, upgrade technology with the change of type and power of lighting on lighting will create energy savings in the use of electricity at the Hotel the Bono Pekanbaru and create a bright and comfortable room. Change the currently installed lights into LED lights so that the lighting system available in each room meets the SNI lighting standard 03-6197-2000.